USING OF SOME HALOORGANOPHOSPHINES AND STUDYING THEIR SYNERGETIC EFFECT WITH CHLORINATED RUBBER TO RETARD FLAMMABILITY AND COMBUSITION OF EPOXYAND UNSATURATED POLYESTER RESINS - Ugal, Jalil; Bahjat, Mohammed (Iraqi Journal of Science, 2024)
Five additives were used in this work namely: tetra ethyl ammonium tribromophenyl phosphine (I), tetra ethyl ammonium chlorodibromophenyl phosphine (II) chlorinated rubber (III), a mixture of 50% by weight of each of I and III (additive IV), a mixture of 50% by weight of each of II and III (additiveV) in order to study the synergetic effect of these compounds as flame retardants with epoxy and unsaturated polyester resins.The results showed that all these additives are active and the synergetic effect was very clear in which the additives IV and V gave the best results. The retarding activity of these compounds is following the order:-IV > V > I > II > IIIThe tests depended on the ASTM ( in which the limiting oxygen index (LOI), rate of burning (R.B) average extent of burning (AEB), average time of burning( ATB) and the maximum height of flame(H) were measured) were used to evaluate the activity of the additives.